Molecular analysis of the neurogenic locus Enhancer of split of Drosophila melanogaster - Knust, Elisabeth (1987)
Enhancer of split [E(spl)], one of the neurogenic loci of Drosophila, is located in bands 96F8-13. One hundred and fifty kilobases of genomic DNA, spanning the E(spl) locus, were cloned by chromosomal walking. DNA heterogeneities associated with eleven E(spl) mutations, including three Pr alleles, were mapped to a region of 36 kb, and an additional one outside of this region. One of these mutations is a deletion of ˜34 kb that causes severe neural hyperplasia of homozygous embryos with complete penetrance. Mutations associated with DNA polymorphisms mapping within smaller regions do not lead to a fully penetrant neurogenic phenotype. The 36-kb region encodes 11 major transcripts, which exhibit distinct temporal and/or spatial patterns of expression. The expression of one of these transcripts is modified in two different mutants. In addition, one of the mutants [E(spl)(D)] shows another transcript, which is not present in the wild-type and co-exists with the remaining transcripts. We suggest that more than one of the 11 transcripts are necessary for a normal function of the E(spl) locus. The spatial distribution of four of these RNAs, which exhibit almost identical patterns of expression, strongly suggests that the encoded proteins are required for the process of segregation of neural and epidermal lineages.